(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Sensing the environment without human intervention is carried out with Wireless Sensor Networks. Thus WSNs have gained impetus in every field as applicable to various sensing applications. As the sensor nodes are very minute with limited power, memory and controlling mechanism. Thus it is necessary to implement energy efficient routing in sensor nodes such that network lifetime is enhanced. In this paper, we have discussed various existing energy efficient routing schemes and made comparison on various parameters in literature survey. Finally came to conclusion that there is a need of an energy efficient routing protocol which can further extend network lifetime. We propose an idea in which existing; Enhanced Energy Efficient Protocol with Static Clustering (EEEPSC) is modified by placing a fraction of nodes having more energy than normal nodes in the locations where Base Station is far away. And BS is placed within the area of deployed nodes.